Commemoration and Cultural Revitalization: The Lifeworld of Montreal’s Hungarian Martyrs Synagogue and Hungarian Jewish Sisterhood - Remz, Sean (Canadian Jewish Studies / Études juives canadiennes, 2024)
Building upon fairly recent scholarship on the reception of Holocaust survivors in Canada and Montreal more specifically, this article examines a synagogue and sisterhood specific to Hungarian Holocaust survivors in Montreal, most of whom arrived in the wake of the 1956 Hungarian Revolution. Holocaust survivor accounts suggest a barrier between them and previously settled Canadian Jews, particularly in the realms of sociability and synagogue life. This barrier was heightened among Hungarians given the language gap, contributing to their impetus for a synagogue of their own, named the Hungarian Martyrs Synagogue. Their Holocaust commemoration events and dances were distinctive in their reverential discourse of martyrdom, and sense of cultural revitalization. The primary source base for this article is the memorial volume of the Hungarian Martyrs Synagogue (which includes commemorative poetry), with insight and context from oral history interviews.